2018
DOI: 10.1177/0958928718805631
|View full text |Cite
|
Sign up to set email alerts
|

Taking the initiative: Direct democracy, coalition governments and welfare state expansion

Abstract: Direct democratic institutions have been adopted in a number of countries since the 1990s, especially in Latin America and Eastern Europe Research on welfare state development and direct democracy holds a pessimistic view: Direct democracy constrains welfare state development (mainly case studies on Switzerland) Research from economics about direct democracy and government spending provides similar findings: Referendums constrain; effect of initiatives is unclear

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Other scholars, in the tradition of Downs (1957), argue that more direct participation, especially in the form of popular initaitives, may lead to more state intervention due to democracies' inherent tendency to redistribute (e.g. Freitag and Vatter, 2006;Asatryan, 2016;Asatryan et al, 2017;Blume et al, 2009;Blume and Voigt, 2012;Walter, 2019). In an encompassing literature review, Matsusaka (2018) finds that financial referendums are consistently observed to have a negative effect on state intervention.…”
Section: Direct Democracy and The Representative Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Other scholars, in the tradition of Downs (1957), argue that more direct participation, especially in the form of popular initaitives, may lead to more state intervention due to democracies' inherent tendency to redistribute (e.g. Freitag and Vatter, 2006;Asatryan, 2016;Asatryan et al, 2017;Blume et al, 2009;Blume and Voigt, 2012;Walter, 2019). In an encompassing literature review, Matsusaka (2018) finds that financial referendums are consistently observed to have a negative effect on state intervention.…”
Section: Direct Democracy and The Representative Systemmentioning
confidence: 99%
“…As a result, they have a strong incentive to employ popular initiatives to increase public spending (in their favour). In addition, it implies that the smaller the number of parties in government, the more likely that societal groups not represented in government will, ceteris paribus, succeed in forming a winning coalition (Walter 2019). In contrast, in the case of large governing coalitions, parties have a narrower voter base and, thus, can externalise a higher share of the costs, which should lead to higher levels of public spending (e.g.…”
Section: Popular Initiativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Armingeon et al. ; Walter , ) or immigration policies and minority rights (Christmann ; Manatschal ). This variation in the institutional setup and public policies allows researchers to exploit cross‐cantonal and temporal differences in policy‐making to address important topics such as tax competition (e.g.…”
Section: Introductionmentioning
confidence: 99%